The ILD-GAP risk prediction model performs poorly in myositis-associated interstitial lung disease. (April 2019) - Brusca, Rebeccah M.; Pinal-Fernandez, Iago; Psoter, Kevin; Paik, Julie J.; Albayda, Jemima; Mecoli, Christopher; Tiniakou, Eleni; Mammen, Andrew L.; Christopher-Stine, Lisa; Danoff, Sonye; Johnson, Cheilonda
Abstract: Purpose: Myositis-associated interstitial lung disease (MA-ILD) is associated with increased mortality, but no prognostic model exists in this population. The ILD-GAP index was developed to predict mortality risk across all subtypes of chronic ILD. The purpose of this study was to validate the ILD-GAP risk prediction model in patients with MA-ILD. Procedures: We completed a retrospective cross-sectional study of patients enrolled in the Johns Hopkins Myositis Center database between 2006 and 2017. Cumulative mortality rates were estimated using the Kaplan-Meier test. Model calibration was determined by using standardized mortality ratios of observed versus expected deaths. Main findings: 179 participants with MA-ILD were included. The mean baseline percent predicted forced vital capacity was 65.2 ± 20.6%, forced expiratory volume in the first second 65.4 ± 20.4%, and carbon monoxide diffusing capacity 61.6 ± 20.0%. Thirty-two participants died (17.9%). The ILD-GAP model had poor discriminative performance and calibration. Conclusions: The ILD-GAP risk prediction model is a poor predictor of mortality among individuals with MA-ILD. The identification of a better predictive model for MA-ILD is needed to help guide care in this patient population. Highlights: The ILD-GAP index has not been validated in individuals with myositis-associated interstitial lung disease (MA-ILD). The ILD-GAP risk prediction model is a poor predictor of mortality among individuals with MA-ILD. The identification of a better predictive model for MA-ILD is needed to help guide care in this patient population.